2022
DOI: 10.1088/2058-8585/ac6719
|View full text |Cite
|
Sign up to set email alerts
|

The integration of electronic circuits in plastics using injection technologies: a literature review

Abstract: A great deal of attention has been paid in recent years to the integration of two and three-dimensional integrated electronic parts into plastics, both for their potential applications in modern human lives and for their outstanding properties, which include the ability to reduce product weight and space while increasing product reliability. The development of integrated electronic devices into plastics is advancing rapidly, owing to advancements in methodology and manufacturing techniques, which have signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Injection moulding technology has been increasingly widely applied in modern industry on account of its high efficiency, manufacturing flexibility, and high level of automation [1][2][3]. However, during injection moulding, due to improper * Author to whom any correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Injection moulding technology has been increasingly widely applied in modern industry on account of its high efficiency, manufacturing flexibility, and high level of automation [1][2][3]. However, during injection moulding, due to improper * Author to whom any correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is sufficient that the electronic systems fit a convenient form factor of the shape into which they will be integrated. Many researchers worked intensively to integrate different electrical functionalities like light emitting diodes (LEDs), light guides, numerous touch switches or slides, and near field communication (NFC) antennas into plastic products using the in-mold process [ 3 , 4 ]. By fabricating optical touch panels, organic light emitting diodes (OLEDs), foils, and disposable healthcare sensors, T. Alajoki et al [ 5 ] demonstrated the feasibility of hybrid in-mold integration.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the integration of electronics in injection-molded parts to manufacture “smart” mechanical, durable and light products cost-effectively has gained traction [ 1 , 2 ]. One way is to adapt the in-mold decoration (IMD) process.…”
Section: Introductionmentioning
confidence: 99%